Factors Affecting Oversubscription Share - Nuryasman MN; Brigitta Brigitta (Jurnal Manajemen, 2022)
The purpose of this study is to analyze the effect of issue price, issue size, firm size, and underpricing on oversubscription on companies that are listed to have conduct Initial Public Offering (IPO) on IDX in the period of 2019 to 2021. This study uses quantitative method with descriptive approach. The samples were selected using purposive sampling method and the results consisted of 138 companies from 2019 to 2021. The data analysis was carried out with Data Panel Regression using EViews 10. The results of this study shows that firm size has a negative and significant effect on oversubscription. While underpricing has a positive and significant effect on oversubscription. On the other hand. issue price and issue size didn’t have any effect on oversubscription.